Peningkatan Pengetahuan Ibu Balita Melalui Edukasi Gizi Seimbang di Posyandu Desa Pagerejo - Putu Ayu Aryanda Parawidnyaningsih; Reza Hesty Viona; Prada Marwah Al Kamilah; Triesta Mystah Istyadzah; I Made Krisna Naradha; Claudia Key; Gere Yusuf Kelly; Ni Kadek Niken Ayu Lestari; M. Raffli Naresca Pradana; Atik Sri Wulandari; Sukma Sahadewa; Ayu Cahyani Noviana (PT. Hasba Edukasi Mandiri, 2026)
Nutritional issues in toddlers remain a public health challenge in Indonesia, particularly related to stunting, malnutrition, and feeding patterns that do not comply with the principles of balanced nutrition. The lack of knowledge of mothers as primary caregivers is one factor contributing to inappropriate child feeding practices. This activity aims to improve the knowledge of mothers of toddlers regarding balanced nutrition through health education at the Pagerejo Village Integrated Health Post (Posyandu). The method used is a participatory educational approach through interactive counseling, discussion, and evaluation using a pre-test and post-test design. The activity was carried out on February 18, 2026, at the Pagerejo Village Health Post (Ponkesdes), involving 30 mothers with toddlers aged 0–5 years. The material provided included the concept of balanced nutrition, the